Determinação de hidrocarbonetos policíclicos aromáticos em lodo de esgoto por cromatografia gasosa acoplada a espectrometria de massas - Natanny Almeida Santos (2016)
Sewage sludge is a solid residue generated during the treatment of wastewater in sewage treatment plants (STPs). After treated and processed, this material can be used in agriculture. However, this practice can lead to contamination and accumulation of toxic pollutants in various environmental compartments. Among these contaminants, the polycyclic aromatic hydrocarbons (PAHs) constitute a class of chemicals compounds commonly present in sewage sludge. In this study, the solid-liquid extraction with purification at low temperature (ESL-PBT) modified has been validated for monitoring of 16 PAHs. The analyzes were performed by gas chromatography and mass spectrometry. For the development and validation of the proposed method is necessary the use of sludge samples free of PAHs, called white. In view of this, samples of different sewage treatment plants were evaluated using the ESL-PBT and analysis by GC-MS. However, in all samples was detected the presence of PAHs and various interfering of the matrix. The alternative found was obtain, in laboratory, sludge samples free of PAHs for subsequent application of ESL-PBT technique. Thus, sewage sludge samples were treated in soxtec with ethyl acetate for 1 hour. The ESL-PBT was conducted using 4.0000 g of sludge treated, 7.00 ml of acetonitrile, 1.00 mL of ethyl acetate, 4.00 ml of water (pH 11), 0.1 g NaCl, and 5 min in vortexing. The extraction percentages ranged from 37% (benzo[k]fluoranthene) to 129% (naphthalene) and relative standard deviation 13% for most PAHs. The limits of quantification were from 0.0025 mg kg-1 to 0.025mg kg-1. The method for determination of PAHs was applied in sewage sludge samples collected in the drying bed of the sewage treatment plant (STP) of the city of Juramento (MG, Brazil). They were detected and quantified 9 PAHs. Therefore, the method is efficient for the determination of PAHs in sewage sludge with potential use in agriculture.